Cross-boundary weed management in protected area–centered ecosystems: how can it work and what makes it harder to achieve?. (2nd September 2021) - Otto, Natalie; Brunson, Mark
Abstract: Invasive species management in natural landscapes is generally executed at the scale of independent jurisdictions, yet the ecological processes and biodiversity to be protected from invasion occur over large spatial scales and across multiple jurisdictions. Jurisdictional land boundaries can influence the flows and dynamics of ecological systems, as well as the social systems that exist in these complex landscapes. Land management entities in large, protected area–centered ecosystems may use different approaches to address cross-boundary management challenges. To understand these differing strategies and their effects on cooperative invasive plant management, we interviewed employees with federal, county, and state agencies, research organizations, nonprofits, and local stakeholder groups in two national parks and their surrounding lands in California, USA. Although all participants stressed the importance of working together, they did so along a continuum of strategies ranging from simple communication to coordination of independent efforts to active collaboration. Barriers to collaboration can be categorized as originating within or externally to the management unit, including limited resources, differing agency priorities, paperwork requirements, and lack of support by higher-level managers. Strategies to reduce barriers depend on where they originate.